A search for geometric-shape objects in a vector image: Scalable Vector Graphics (SVG) file format - Chanon Seel-Audom (2018)
© 2017 IEEE. This paper proposes a model for detecting objects with geometric shapes in an image whose file format is SVG (Scalable Vector Graphics). The SVG is known as a type of vector images. A major interesting feature of SVG is that components in victor images are created using mathematical theories and equations, in addition, vector images have many more advantages over raster images in various aspects. Moreover, an object's details in a human's sight, a triangle for example, is looked as it has three corners. But the true shape created in SVG of the object may be different from the human's limited sight. Observing these gaps or limitation, we thus propose alternatively simple methods for processing on objects with geometric shapes directly in a vector image without loss of any details in its original form.